Structural features of the two-component system LisR/LisK suggests multiple responses for the adaptation and survival of Listeria monocytogenes - Arenas Suarez, Nelson; Department of Biochemistry and Molecular Biology. University of Southern Denmark campusvej 55. 5230 Odense M, Denmark (2013)
Here, we characterized the structure of the two-component regulatory system, LisR/LisK, in Listeria monocytogenes. To predict the structure of both proteins and the relationship between them, we employed several bioinformatic tools and databases. Based on our results, LisK protein is embedded in the cell membrane and its modular composition (HAMP, histidine kinase and ATPase domains) is associated with its autophosphorylation (His-266). A stimulus-response likely determines the sequential signal propagation from the bacterial cell surface to its cytoplasmic components. According to our results, LisR is a cytoplasmic protein with a receptor domain (homologous to CheY) that comprises a phosphoacceptor residue (Asp-52) and a DNA-binding domain, which may allow the transmission of a specific transcriptional response. LisR/LisK has been experimentally characterized both biochemically and functionally in other Bacilli pathophysiology; our structure-function approach may facilitate the design of suitable inhibitors.